2018
DOI: 10.1016/j.neuroimage.2017.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Brain state expression and transitions are related to complex executive cognition in normative neurodevelopment

Abstract: Adolescence is marked by rapid development of executive function. Mounting evidence suggests that executive function in adults may be driven by dynamic control of neurophysiological processes. Yet, how these dynamics evolve over adolescence and contribute to cognitive development is unknown. In a sample of 780 youth aged 8-22 yr (42.7% male) from the Philadelphia Neurodevelopment Cohort, we use a dynamic graph approach to extract activation states in BOLD fMRI data from 264 brain regions. We construct a graph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 106 publications
3
43
0
Order By: Relevance
“…Emerging data demonstrate the time-varying properties of FC change across years of childhood to support a remarkable range of emerging cognitive abilities (Marusak et al, 2017). For instance, previous studies revealed age-related development in the frequency and dwelling time (how long the brain spends on a given mode) of specific FC "modes" Hutchison and Morton, 2015;Qin et al, 2015;Marusak et al, 2017;Medaglia et al, 2018) and between-state transitions from late childhood to young adult Qin et al, 2015). Such developmental changes in the dynamic FC are related to the reduced behavioral variability and more accurate performance (McIntosh et al, 2008).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Emerging data demonstrate the time-varying properties of FC change across years of childhood to support a remarkable range of emerging cognitive abilities (Marusak et al, 2017). For instance, previous studies revealed age-related development in the frequency and dwelling time (how long the brain spends on a given mode) of specific FC "modes" Hutchison and Morton, 2015;Qin et al, 2015;Marusak et al, 2017;Medaglia et al, 2018) and between-state transitions from late childhood to young adult Qin et al, 2015). Such developmental changes in the dynamic FC are related to the reduced behavioral variability and more accurate performance (McIntosh et al, 2008).…”
Section: Introductionmentioning
confidence: 84%
“…Many behavioral studies have presented various emerging high-order cognitive functions in the first a few years of life, such as self-awareness (Amsterdam, 1972), spatial attention (Haith et al, 1988), and working memory (Reznick, 2008). All these skills request better cognitive flexibility, controllability, adaptivity for brain regions to accommodate and adapt to quickly changing environments (Medaglia et al, 2018). For example, to respond to the internal (i.e., feelings about self) and external stimuli (i.e., multimodal sensory input from the environment) promptly, the task control and attention control regions in the infant brains are more likely to become increasingly variable with increased FC flexibility, i.e., their FC profiles could be more variable, linking different functional systems at different time for their coordination and communication.…”
Section: Gradually Increased Global Functional Flexibility In Early Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the above methods has indicated that network dynamics are relevant to psychological processes. For example, research has yielded early evidence that network dynamics are associated with individual differences in development (Faghiri, Stephen, Wang, Wilson, & Calhoun, ; Hutchison & Morton, ; Marusak et al, ; Tian, Li, Wang, & Yu, ) and cognitive functioning (Cohen, ; Kaiser et al, ; Medaglia et al, ), and can provide insight into mental health (Damaraju et al, ; Kaiser et al, , ; Kaiser, Snyder, et al, ; Ma, Calhoun, Phlypo, & Adali, ; Rashid et al, ; Rashid, Damaraju, Pearlson, & Calhoun, ). However, more work is needed to evaluate the reliability of the spatial organization of TNS, and to understand the extent to which these properties are common across people or time.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, numerous studies in adults have shown evidence for the dynamic nature of FC characterized by the variations of connection strengths, the sign of interactions or changes in node membership among modules Hutchison et al (2013) during task conditions as well as rest Calhoun et al (2014). Further such transient nature of brain network is reported to increase over development Chai et al (2017), and directly related with learning Bassett et al (2011), task performance Shine et al (2016); Keerativittayayut et al (2018), executive functions Medaglia et al (2018), and in general, with healthy cognitive functioning Thomas Yeo et al (2011) including general intelligence Barbey (2018) and creativity Li et al (2017); Sun et al (2018)…”
Section: Introductionmentioning
confidence: 99%